The determinants of foreign direct investment in Malaysia / Muhammad Fahmie Md Yatem - Md Yatem, Muhammad Fahmie (2016)
This research will focus on factor influences foreign direct investment inflow in Malaysia. The objective of this research is to examine the relationship between exchange rate, infrastructure, market size, inflation and foreign direct investment inflow in Malaysia. This research paper is based on the yearly data from 1986-2015. The variables involved in this study are foreign direct investment inflow in Malaysia, exchange rate, infrastructure, market size and inflation. The data tested on coefficient of correlation, coefficient of determination, t-statistic, f-Statistic, Durbin Watson and multicollinearity. Based on findings, some of the independent variables are found to be significant and some are not significant. In short, market size and inflation has significant relationship towards foreign direct investment inflow. However official real effective exchange rate and infrastructure is not significant towards foreign direct investment inflow